T indak Tutur Representatif dan Direktif dalam Lirik Lagu Didi Kempot (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2021)
Communication event is a medium to express ideas, thoughts, intentions, and reality. The form of music and lyric can be understood as one form of mass communication events. Songs and lyrics contain language of human expression produced through a creative process. Therefore, they are loaded with meaning that needs to be translated. Pragmatics concerns on the meaning of language. This qualitative research aims at describing the lyric meanings in Didi Kempot’s songs by using a pragmatic approach, especially by employing Searle’s theory of speech acts. This research analyzes five songs entitled Banyu Langit, Kangen Nickerie, Pantai Klayar, Tanjung Mas Ninggal Janji, and Kalung Emas. The findings show that representative and directive speech acts appear 22 times and 8 times respectively. The former includes utterances of stating, suggesting, complaining, and claiming. The latter includes asking, ordering and begging. The type of speech act that most frequently occurs is complaining.
Keywords: Directives; Pragmatics; Representatives; Speech Acts